Expectations of Faculty of Nursing Schools in Tehran on Administrative Management of Schools: A qualitative study - Abolfazl Rahimi; Abbas Ebadi; Hosein Mahmoudi; Ahmad Mahdizade (Tehran University of Medical Sciences, 2012)
Background & Aim: Motivated faculty promotes nursing students' educational level which leads to community health promotion. Attempts should be made to recognize and analyze motivating factors including expectations. This qualitative study attempted to clarify expectations of faculty of Tehran nursing schools on management system. Methods & Materials: This was a qualitative study. The participants were 14 nursing faculty members of Tehran, Shahid Beheshti, Artesh, Shahed, and Baghiatallah Universities located in Tehran. Purposive sampling was used to recruit the participants. Data were collected using semi-structured interviews with the participants. Qualitative content analysis was used to analyze the data. Results: Expectations of nursing faculty were explained in eight categories: empowerment of the faculty, organizational support, fairness, appropriate performance evaluation, providing appropriate working conditions, applying appropriate management strategies, attention to welfare and financial problems and promoting quality of education and research. Conclusion: Understanding the expectations of the nursing faculty and trying to meet them can improve performance of the faculty. Meeting these expectations can enhance motivation and job satisfaction among the faculty.